Establishment of a 3D model of tumor-driven angiogenesis to study the effects of anti-angiogenic drugs on pericyte recruitment. (17th June 2021) - Qiu, Yaqi; Wang, Ning; Guo, Tingting; Liu, Shoupei; Tang, Xianglian; Zhong, Zhiyong; Chen, Qicong; Wu, Haibin; Li, Xiajing; Wang, Jue; Zhang, Shuai; Ou, Yimeng; et al.
Abstract : A 3D tumor-driven angiogenesis model incorporating endothelial cells and pericytes was established to investigate the effects of anti-angiogenic agents on pericyte recruitment in a rapid and reproducible way. Abstract : Hepatocellular carcinoma (HCC), as a well-vascularized tumor, has attracted increasing attention in antiangiogenic therapies. Notably, emerging studies reveal that the long-term administration of antiangiogenic drugs induces hypoxia in tumors. Pericytes, which play a vital role in vascular stabilization and maturation, have been documented to be associated with antiangiogenic drug-induced tumor hypoxia. However, the role of antiangiogenic agents in regulating pericyte behavior still remains elusive. In this study, by using immunostaining analysis, we first demonstrated that tumors obtained from HCC patients were highly angiogenic, in which vessels were irregularly covered by pericytes. Therefore, we established a new 3D model of tumor-driven angiogenesis by culturing endothelial cells, pericytes, cancer stem cells (CSCs) and mesenchymal stem cells (MSCs) with microcarriers in order to investigate the effects and mechanisms exerted by antiangiogenic agents on pericyte recruitment during tumor angiogenesis. Interestingly, microcarriers, as supporting matrices, enhanced the interactions between tumor cells and the extracellular matrix (ECM), promoted malignancy of tumor cells and increased tumor angiogenesis within the 3D model, as determined by qRT-PCR and immunostaining. More importantly, we showed that zoledronic acid (ZA) reversed the inhibited pericyte recruitment, which was induced by sorafenib (Sora) treatment, through fostering the expression and activation of ErbB1/ErbB2 and PDGFR-β in pericytes, in both an in vitro 3D model and an in vivo xenograft HCC mouse model. Hence, our model provides a more pathophysiologically relevant platform for the assessment of therapeutic effects of antiangiogenic compounds and identification of novel pharmacological targets, which might efficiently improve the benefits of antiangiogenic treatment for HCC patients.